A highly efficient heterogeneous montmorillonite K‐10‐supported palladium catalyst for Suzuki–Miyauracross‐coupling reaction in aqueous medium. (2nd October 2014) - Gogoi, Ankur; Chutia, Sankar Jyoti; Gogoi, Pradip K.; Bora, Utpal
<x xml:space="preserve">Abstract</x> A heterogeneous montmorillonite K‐10‐supported palladium triphenylphosphine catalyst is reported for the Suzuki–Miyauracross‐coupling reaction at room temperature. A library of electronically diverse aryl bromides and arylboronic acids underwent the cross‐coupling reaction at very good rates in aqueous solvent. The reusability of the catalyst was also examined and it was found to be effective up to three catalytic cycles. Copyright © 2014 John Wiley & Sons, Ltd.